Contesting Religious Beliefs: The Experience of the Cham in Vietnam - Beti Rosita Sari (International Journal of Interreligious and Intercultural Studies, 2019)
Studies on Islam and Muslims in Vietnam are indeed very interesting to be understood and shared with other Muslims in the region. Historically, the Cham communities in Vietnam have converted over many years from Hinduism to Buddhism and to Islam. Today, the Cham communities are often associated with Islam, but this does not mean that they are all practicing the same rituals. However, even though they have different beliefs and orientations, the interactions among the Cham in their own community are still in harmony. I will argue that the differences between ethnic identities and religious orientations among the Cham in Vietnam have been influenced by their interactions with outsiders and their transnational networks. This study tries to capture the religious orientations among the Cham in Vietnam and how they maintain their harmonious livelihood and social interaction in the community. Furthermore, it takes a qualitative approach through observations, in-depth interviews and review literature. The observations and in-depth interviews occurred in May-June 2014 in Ho Chi Minh City and Phan Rang Province in Central Vietnam.